ANALISIS FAKTOR PENYEBAB KETERLAMBATAN REPAIR ROLLER FAIRLEAD DENGAN METODE KMO DAN RCA PADA KAPAL ABC - Pramoedya Nugroho, Aldi; Syaifullah, Hafid (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
Ship transportation is a very important tool for the sustainability of the maritime industry. Considering the importance of using ships, regular repairs are needed on ship components, one of which is the roller fairlead. Repairs to the roller fairlead on the ABC ship, which were originally only scheduled for 7 working days, were delayed by up to 38 working days. Therefore, this research aims to analyze the factors causing delays in the roller fairlead repair process on ABC Ships carried out by PT XYZ. Data collection was carried out by conducting direct interviews and distributing questionnaires to related parties. The data that was collected was processed using the Kaiser-Meyer-Olkin (KMO) and Root Cause Analysis (RCA) methods to identify and analyze the root causes of delays. The results of the analysis show that the main factor causing delays is a lack of labor allocation with a mean value of 4.38. Based on the results of this analysis, suggestions for improvement are given using the fishbone diagram tool. In this way, PT XYZ is expected to be able to increase work effectiveness, so that similar incidents do not happen again in future projects